(3cJGH eHGOF Cgd GdeOjfI GdaGVdIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s ((3jMi Hf YHO GdeSjM GdeJWHH s)
(3ChdgG (B:s
(3Gdbhd ai GdTF GdPjfHZi Cf jYJbO ajg Cfg gh Gdgd eGgh hcja gh HeGPG jfHZi Cf jhUa s
(3BNQgG (B:s
(3agPG jMJGL Cf jeSM ai cd SfI eG hQY ajgG hcdeG JbOe ai eSGMI Pdc cGf GbQH Edi GYQGV GdeJYdbjf Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJH HNW bdjd GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs